Pengaruh Kompos Mucuna bracteata Dan Azotobacter Terhadap Pertumbuhan Dan Kadar Nitrogen Bibit Kelapa Sawit - Wahyuni, Mardiana; Triani, Agus; Sembiring, Mariani (Universitas Medan Area, 2020)
Through the nursery process with certain treatments can be produced quality seeds. Application of Mucuna bracteata compost and Azotobacter on growing media in polybags is one alternative that expected to increase plant growth. This study aimed to determine the effect of M. bracteata compost and Azotobacter and its combination on growth and nitrogen levels of oil palm seedlings. This research was conducted at STIPAP Medan in December 2018 - June 2019 with a Factorial Randomized Block Design (RBD). Treatment compost (K) 3 levels ie K0, K1 and K2 and Azotobacter (A) with 3 levels are A0, A1 and A2. M. bracteata treatment had a very significant effect on seedling height, number of leaves, shoot dry weight and root dry weight. Azotobacter treatment did not significantly affect the parameters of observation, increasing levels of leaf N 13-15%. Interaction compost and Azotobacter treatment had no significant effect. The best treatment is the K2A2 of 1.2 kg of compost and 30 ml of Azotobacter each oil palm seedlings planted in the polybag.